CRIMINOLOGY AS A SCIENCE AND ACADEMIC DISCIPLINE: TOWARDS THE ESSENCE THROUGH ATTRIBUTES (Bulletin of criminological association of Ukraine, 2023)
This work reflects various criminological schools and approaches of Ukrainian criminology, which form the necessary symbiosis/baggage of knowledge for a deeper understanding/awareness of the essence of criminology. If Western criminologists firmly stand on positivist, sociological positions, then we should transform Ukrainian criminology into an integrative/complex approach reflecting many spiritual and value meanings, which are especially relevant during the current Russian-Ukrainian war. It is important to note that the questions posed in this article, as a result of the applied method of «dialogical representation», are answered fragmentarily by prominent scientists of our country and the world. The teacher can ask questions to the audience from a wide variety of fields of knowledge. Therefore, we have somewhat disrupted the logical sequence of presenting certain questions in order to avoid monotony, to keep the reader in the tone/rhythm of constant attention and surprise of completely different questions, which are placed in a chaotic order and relate to the first topic: «Criminology as a science and an academic discipline». Today, such areas of criminology are actively being developed through the prism of interdisciplinarity as: political criminology, war criminology, sports criminology, criminology, penitentiary criminology. From here, perhaps, the passport of the specialty 12.00.08 should be revised. First of all, a new specialty should be opened in our country - “criminologist”, similar to a psychologist, so that everyone who wishes can deeply master many criminological meanings and gain the appropriate level of knowledge.
Keywords: criminology; subject; interdisciplinarity; crime; determination; personality of a criminal offender; combating crime; background; method of «dialogical representation»